Usages et mésusages de la bibliométrie en économie - Florence Audier (Revue de la Régulation)
The place given to bibliometrics in Economics, as well as the role assigned to US journals in the hierarchy of publications which support the evaluation of researchers as well as their teams, invite us to take seriously into account how French economists use them. Hence the double question: who publishes in which journal, and with whom? The investigation concerns the authors of all the articles published during 4 years (from 2015 to 2018) in the six journals rank 1* (the excellent ones) appearing in the list of CoNRS, as well as the authors of all the articles published in 2015 by the 56 journals classified « 1 ». At the end of the survey, it is clear that French economists do not (almost) have access to publishing in journals which they have nevertheless designated as targets to be reached, and recommended as a criterion of excellence. To shed light on this a priori paradoxical situation, given the challenges posed by individual and collective evaluations, we must return to the genesis of such a situation, and its consequences.